Experimental and numerical study on the cooling performance of heat pipe assisted composite phase change material-based battery thermal management system. (15th November 2022) - Feng, Renlang; Huang, Peifeng; Tang, Ziyi; He, Yanyun; Bai, Zhonghao
Highlights: The heat pipe can help dissipate the stored heat inside the PCM during cycling. The hybrid system can effectively manage warming trends and uniformity. The structure is designed for thermal safety and energy density. A copper foam porosity of 40% to 50% improves cooling efficiency. Depending on the operational conditions, various hybrid systems are suggested. Abstract: The phase change material (PCM) cooling system is considered a promising battery thermal management system due to its high energy conservation and simple structure. However, its development is restricted to the low thermal conductivity of PCM and the difficulty in heat dissipation over time. And the applicable border of the PCM cooling system is also unclear. This paper gives a comprehensive study and optimization design of a hybrid cooling system combining the composite PCM and flat heat pipe (composite PCM-HP) for the actual application. The thermal performance and applicable border of this hybrid system were investigated through orthogonal tests. The experimental results show that composite PCM (CPCM) system and composite PCM-HP hybrid system can control temperature rise and uniformity well. Compared to the thermal performance of the air-cooling system, the maximum temperature in the hybrid system is 22 °C lower when it is discharged at a 2C rate under 25 °C. The applicable border of the hybrid system is tested at a 2C discharge rate under 40 °C, where the maximum temperature exceeds the allowable temperature range. The flat heat pipe presents excellent auxiliary heat dissipation for CPCM in the cycling tests at 40 °C, which makes the maximum temperature 10 °C lower than the CPCM system and 15 °C lower than the air-cooling system. A lumped thermal model for the hybrid system was developed and validated and further analyzed the effects of the dimension size, the porosity of copper foam, and the convective heat transfer coefficient on thermal performance. In light of the permitted temperature range, volume energy density, cooling performance, and operational circumstance, the best designs for these criteria are recommended.